Dose‐intensive chemotherapy including rituximab in Burkitt's leukemia or lymphoma regardless of human immunodeficiency virus infection status. Issue 9 (29th January 2013) - Ribera, Josep‐Maria; García, Olga; Grande, Carlos; Esteve, Jordi; Oriol, Albert; Bergua, Juan; González‐Campos, José; Vall‐llovera, Ferran; Tormo, Mar; Hernández‐Rivas, Jesús‐Maria; García, Daniel; Brunet, Salut; et al.
Abstract BACKGROUND: The use of rituximab together with intensive chemotherapy in Burkitt's lymphoma or leukemia (BL) has been scarcely explored. This study prospectively evaluated and compared the outcome and toxicity of human immunodeficiency virus (HIV)‐positive and HIV‐negative patients with BL who were treated in an intensive immunochemotherapy‐based and age‐adapted trial. METHODS: A total of 118 adult patients (80 HIV‐negative and 38 HIV‐positive) aged 15 to 83 years were treated with 4 (nonbulky stages I‐II) or 6 (stages II bulky, III‐IV) cycles of intensive chemotherapy combined with rituximab. Reduction in chemotherapy doses and modification of the cycle schedules was performed in patients older than 55 years. RESULTS: The clinical characteristics of HIV‐positive patients were comparable with those who were HIV‐negative. Complete remission rates were 82% and 87%, respectively, and 9 patients died in induction, 9 died in remission, and 7 relapsed. After a median follow‐up of 2.5 years, nonsignificant differences were observed in the 4‐year disease‐free survival and overall survival (OS) probabilities (77% and 63% for HIV‐positive and 80% and 78% for HIV‐negative patients, respectively). Young HIV‐infected patients presented higher incidences of grade 3 or 4 mucositis and severe infectious episodes. Poor general status and bone marrow involvement, but not advanced age, were associated with a shorter OS, allowing the definition of 3 prognostic groups, with the OS ranging from 50% to 92%. CONCLUSIONS: Age‐adapted intensive immunochemotherapy is highly effective in both HIV‐negative and HIV‐positive patients, with a higher toxicity in the latter group. Poor general status and bone marrow involvement had a negative impact on survival. Cancer 2013. © 2013 American Cancer Society.